Immune‐related Adverse Events in Cancer Patients. (25th May 2018) - Pallin, Daniel J.; Baugh, Christopher W.; Postow, Michael A.; Caterino, Jeffrey M.; Erickson, Timothy B.; Lyman, Gary H.
Abstract: The U.S. Food and Drug Administration has approved immune checkpoint inhibitors and chimeric antigen receptor T cells (CAR‐T cells) as immunotherapy strategies for cancer. These therapies cause a wide variety of adverse events, which mimic other disease states and may emerge months after completion of treatment. This is important because ascertaining a past medical history of cancer treatment within the past year becomes necessary for many presentations. This narrative review summarizes the biology, pathophysiology, and adverse events associated with checkpoint inhibitors and CAR‐T cells and provides a rational approach to management. Proper treatment begins with heightened awareness, rapid diagnosis, and discussion with the patient's oncologist. Treatment of these adverse effects requires only corticosteroids, infliximab, tocilizumab, or fluids or vasopressors when clinically indicated.